Tactical and technical indicators of boxers with different fighting styles - Demchenko Yu.V.; Golovlev V.A.; Yatsin Y.V.; Salnikov V.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the characteristics of striking actions in accordance with individual styles of fighting with special training. Methods and structure of the study. The article examines the dynamics of technical and tactical actions (characteristics of striking actions) among boxers who differ in the style of fighting. The indicated characteristics of special training (free work) were studied using the electronic punching bag “KIKTEST-100”, using the “Kicktester” program. Voluntary work was assessed by the following indicators: 1) impact force; 2) sharpness of the blow; 3) impact energy; 4) number of blows; 5) total tonnage; 6) maximum impact force; 7) maximum sharpness of impacts; 8) maximum impact energy; in 3-minute free work, on a boxing bag. Results and conclusions. The implementation of technical and tactical actions of boxers is to a certain extent connected with the stylistic characteristics of combat operations, the severity of which manifests itself in accordance with the individual psychological characteristics of the boxers. In particular, in the conditions of free work, it was revealed that higher dynamics of the studied striking actions are characteristic of boxers implementing the knockout style, in comparison with tempo fighters and, especially, with boxers implementing the play style of fighting. At the same time, differences in the implementation of fighting styles are largely associated with the individual psychological characteristics of boxers.